1996
DOI: 10.1210/endo.137.6.8641169
|View full text |Cite
|
Sign up to set email alerts
|

Human endometrial fibroblasts immortalized by simian virus 40 large T antigen differentiate in response to a decidualization stimulus.

Abstract: Human endometrial fibroblasts have been immortalized by infection with simian virus 40 large T antigen and established as a permanent cell line, St-2. Biochemical differentiation of this cell line has been demonstrated by the ability of a decidualizing stimulus, 8-bromo-cAMP plus medroxyprogesterone acetate (MPA), to induce PRL secretion and increase the enzymatic activity of estrone sulfatase. MPA, alone or in combination with estradiol, was unable to elicit this response, but potentiated the effect of 8-brom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…To assess the effects of chlamydial infection on the decidualisation of primary endometrial stromal cells, an in-vitro decidualisation method previously described was used 32 . Cells were trypsinised, spun for 3.5 minutes at 800 rpm and resuspended phenol red-free RPMI 1640 with 10% CSFCS.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the effects of chlamydial infection on the decidualisation of primary endometrial stromal cells, an in-vitro decidualisation method previously described was used 32 . Cells were trypsinised, spun for 3.5 minutes at 800 rpm and resuspended phenol red-free RPMI 1640 with 10% CSFCS.…”
Section: Methodsmentioning
confidence: 99%
“…The treated endometrial cells acquire the characteristic morphologic phenotype of decidual cells and express decidual cell-specific markers such as prolactin and insulin-like growth factor binding protein-1 (IGFBP-1). Decidualization can also be induced in primary cultures of human decidual fibroblasts (36) and in a permanent cell line of human endometrial fibroblasts (St-2 cells) (8). Treatment of primary cultures of decidual fibroblasts and St-2 cells with cAMP induces prolactin gene expression and decidualization, but treatment with progesterone, alone or in combination with estradiol, is without effect.…”
mentioning
confidence: 99%
“…Previous studies of prolactin gene expression in endometrial cells have been performed in primary cultures of human endometrial LTo whom correspondence should be addressed at Division of Endocrinology, Children's Hospital Medical Center, 3333 Burner Avenue, Cincinnati, Ohio 45229-3039. stromal cells and in the St-2 endometrial cell line described by White and coworkers (6). Studies in both the primary endometrial stromal cell cultures and the St-2 cell line have shown that the prolactin gene is not expressed until the cells have been exposed to hormones or other factors that induce the cells to decidualize.…”
Section: Introductionmentioning
confidence: 99%
“…The differences in regulation are due in large part to the fact that decidual prolactin is regulated by an alternative promoter located 5' of an additional noncoding exon (exon la) located approximately 6 kilobases (kb) upstream of the pituitary prolactin transcription initiation site (9,16). The decidual type prolactin promoter is also used by other extrapituitary cells that express protactin, such as lymphocytes (2,6,11), myometrial ceils (3) and cyclic AMP-treated decidual fibroblasts (19) and dermal fibroblasts (20).…”
Section: Introductionmentioning
confidence: 99%